Answer: X = -166 Y = 34
Step-by-step explanation: There are a few ways to solve this, I will be showing substitution and will be starting with the first equation
1. Solve for x in the first equation
5(x + 2y) - 3 = 3x + 5
5x + 10y - 3 = 3x + 5
2x + 10y = 8
2x = -10y + 8
x = -5y + 4
2. Plug in the value for x into the second equation
4(x - 3y) - 50 = -33y
4([-5y + 4] - 3y) - 50 = -33y
4(-8y + 4) - 50 = -33y
-32y + 16 - 50 = -33y
-34 = -y
y = 34
3. Plug in the value for y into either equation to solve for x (you can use your simplified x expression to make things easy)
x = -5y + 4
x = -5(34) + 4
x = -166
4. Check values are correct by plugging in the values into the original two equations and making sure they are correct
5([-166] + 2[34]) - 3 = 3(-166) + 5
-493 = -493
4([-166] - 3[34]) - 50 = -33(34)
-1122 = -1122